The Black Prince and the grande chevauchée of 1355 - Madden, Mollie M. (Warfare in history., 2018)
On 19 September 1356 Edward of Woodstock, known as the Black Prince, and his Anglo-Gascon army defeated Jean II of France at the Battle of Poitiers. The victory was the culmination of an expedition which had begun in England in 1355, and saw the successful undertaking of the so-called "grande chevauchee"--Which depended on a system of purveyance and recruitment in England, in addition to an efficient supply train which accompanied the army. This book examines in detail the efficient and effective logistics that drove that success; it also shows the powerful connection between tactics and strategy on the one hand, and geography, human topography, and the need for food, water and rest, on the other